1985
DOI: 10.20506/rst.4.1.190
|View full text |Cite
|
Sign up to set email alerts
|

Aujeszky's disease : factors important for epizootiology and control

Abstract: In Europe it is widespread and only a few countries are free from the disease. AD virus (ADV) is fairly resistant to heat and very stable at normal temperatures and in the cold. Its pH stability ranges from 5.0 to 12.0. The most efficient disinfectants are chemicals that liberate chlorine, and formaldehyde. NaOH is less effective. Lime is recommended for disinfection of slurry. Because of its pH and temperature stability, ADV is very resistant to natural environmental conditions. Pigs are the primary host of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There is evidence that the viruses from modified live vaccine (MLV) can be shed from the oronasal cavity [ 40 ], but Terpstra and Pol [ 41 ] showed that vaccination with MLV vaccines was not likely to interfere with the laboratory diagnosis of ADV field strains. However, since the attenuated virus replicates in the body and can be excreted, transmission to other animals, reverse mutations and genetic recombination with field strains cannot be excluded [ 42 ]. The most commonly used AD vaccine in Serbia for domestic pig vaccination is made using the attenuated Bartha strain, which minimizes field virus excretion comparing to inactivated vaccines [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the viruses from modified live vaccine (MLV) can be shed from the oronasal cavity [ 40 ], but Terpstra and Pol [ 41 ] showed that vaccination with MLV vaccines was not likely to interfere with the laboratory diagnosis of ADV field strains. However, since the attenuated virus replicates in the body and can be excreted, transmission to other animals, reverse mutations and genetic recombination with field strains cannot be excluded [ 42 ]. The most commonly used AD vaccine in Serbia for domestic pig vaccination is made using the attenuated Bartha strain, which minimizes field virus excretion comparing to inactivated vaccines [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very high viral concentrations have been reported in semen ranging from 10 8 to 10 9 TCID 50 per ml (Medveczky & Szabo, 1981) to 10 3.7 to 10 4.9 TCID 50 per ml (Vannier & Gueguen, 1979). Transient viral excretion for up to 12 days usually occurs during the acute phase of the disease (Ressang, 1973) but viral excretion has been observed for long periods of time after natural infection (Wittmann, 1985). After experimental PRV infection by the intratesticular route, testicular degeneration and transient elevation in sperm abnormalities have been reported (Hall, Jr. et al, 1984a;Larsen et al, 1980).…”
Section: Pseudorabies Virusmentioning
confidence: 99%
“…Winds are usually stronger and the atmospheric turbulence is greater during the day than at night; thus, the concentration of infectious virus carried downwind is higher at night (26). E 5 For intranasal infection, piglets require 10 1 -10 3 TCID 50 , young pigs approximately 10 4 TCID 50 and adult pigs 10 4 -10 5 TCID 50 (44,45). E 6 For intranasal infection, cattle require at least 10 5 TCID 50 (44).…”
Section: Ementioning
confidence: 99%
“…E 5 For intranasal infection, piglets require 10 1 -10 3 TCID 50 , young pigs approximately 10 4 TCID 50 and adult pigs 10 4 -10 5 TCID 50 (44,45). E 6 For intranasal infection, cattle require at least 10 5 TCID 50 (44). E 7 Drying of PRV on glass at both 1°C and 22°C at 40-50% relative humidity resulted in a loss of 4 log 10 of virus, i.e.…”
Section: Ementioning
confidence: 99%